The incidence of relapse tuberculosis and its determinants among Tuberculosis patients in Bangkok - Sinsap, Manthana; Hoomkam, Nontiya; Chompook, Pornthip; Chompook, Pornthip (Journal of Medicine and Health Sciences, 2022)
Abstract Thailand was ranked as the 14th most tuberculosis-burdened country in the world. The incidence rate of new tuberculosis (TB) cases in Thailand was approximately 1.3 times higher than global trends with an increasing trend of cases of drug-resistant TB. Based on the implementation of TB control in Thailand from 2002 to 2016, the average success rate for TB treatment was 78.87%. The main causes of unsuccessful TB treatment were a lack of medication, treatment failure and loss of follow-up. This unsuccessful TB treatment has resulted in an increase in the number of relapsed patients. In 2016, 2,514 relapsed cases were reported. There was also a greater recurrence of TB in densely populated and congested urban areas. This study aimed to estimate the incidence and identify the factors associated with cases of TB relapse in Bangkok. The data were collected from the databases of the National Tuberculosis Information Program from January 1, 2014 to November 31, 2018. The data were analyzed using the Kaplan–Meier method to estimate the incidence density and the multivariable Cox regression model was used to identify the factors associated with TB relapse and presented by hazard ratio (HR) with 95% confidence intervals (CIs). Of the 13,707 TB cases were included in this study, the mean age was 44.58 ± 16.91 years old and were predominantly male (60.81%). The incidence rate for relapse was 6.25 per 1,000 person-years (95% CIs= 5.48 - 7.13), and the median time for a TB relapse was 2.48 (interquartile range=0.16-4.91). In the multivariate analysis, TB relapse was independently associated with body weight at treatment initiation less than 50 kg (adjusted HR =1.46, 95% CI= 1.07-2.00), Diabetes mellitus (adjusted HR=3.01, 95% CI=1.83-4.96), and HIV infection (adjusted HR=2.12, 95% CI= 1.45-3.11). In conclusion, the screening for underweight TB patients (less than 50 kg) with co-morbidities may help to identify patients at a high risk of relapse. Therefore, the standard care and treatment of TB patients with these co-morbidities may need close monitoring to prevent and reduce the number of TB relapses.